Trace element data covering 96-7 ka BP from stalagmite CM (Santo Tomas Cave, Cuba) - Sophie F Warken; Denis Scholz; Christoph Spötl; Klaus Peter Jochum; Jesus M Pajon; André Bahr; Augusto Mangini (PANGAEA, 2020)
We present a new speleothem trace element and stable isotope record, which extends previous paleoclimate evidence from Cuban speleothems to the last 96 ka. Stable isotope samples were micromilled at a resolution of 0.10-0.33mm, and measured using an IRMS equipped with a Gasbench. Line scans of Element/Calcium ratios of the speleothem were measured by laser ablation ICPMS and were reduced to the resolution of the stable isotope records.